2014
DOI: 10.6061/clinics/2014(04)07
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen and thrombin concentrations are critical for fibrin glue adherence in rat high-risk colon anastomoses

Abstract: OBJECTIVE:Fibrin glues have not been consistently successful in preventing the dehiscence of high-risk colonic anastomoses. Fibrinogen and thrombin concentrations in glues determine their ability to function as sealants, healers, and/or adhesives. The objective of the current study was to compare the effects of different concentrations of fibrinogen and thrombin on bursting pressure, leaks, dehiscence, and morphology of high-risk ischemic colonic anastomoses using fibrin glue in rats.METHODS:Colonic anastomose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The Bp value among the peritoneal graft-coated group and control group at 15 th days post-operation was significantly different, which indicates that the coating of the injured site of the anastomosis with peritoneal graft increased the strength of the anastomotic site. These results are in agreement with others who reported a significant increase in strength and Bp of the anastomotic area after reinforcing with tissue graft [28,34,35]. However, there were differences in Bp between the 7 th and 15 th days groups but this difference was not significant.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The Bp value among the peritoneal graft-coated group and control group at 15 th days post-operation was significantly different, which indicates that the coating of the injured site of the anastomosis with peritoneal graft increased the strength of the anastomotic site. These results are in agreement with others who reported a significant increase in strength and Bp of the anastomotic area after reinforcing with tissue graft [28,34,35]. However, there were differences in Bp between the 7 th and 15 th days groups but this difference was not significant.…”
Section: Discussionsupporting
confidence: 92%
“…Also, in another study, the deserosalization in the anastomosis site resulted in improved mechanical strength and collagen deposition [12]. While in rats, it has been suggested that the abrasion of the serosal layer of intestinal edges and anastomosed by inverted technique does not reduce leakage and did not increase the mechanical strength of the anastomotic site [28]. Therefore, we designed this experiment to study the effect of peritoneal graft in decreasing the complication of deserosalization.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of inflammatory cells, wound repair cells, extracellular matrices (ECMs) and cytokines participate in the process of healing. Collagenous fibers that exist in mucosa, submucosa and serosa, act as biomechanical fixed points, and are particularly important in the healing of anastomosis 22 23 24 25 . Collagen I contribute to the formation of mature scar tissue, which is mainly responsible for the mechanical tissue stability, whereas collagen III is always found mainly during the early phases of wound healing 26 .…”
mentioning
confidence: 99%
“…In addition, the often-poor adhesion of these matrices, which can be compromised by their low fibrinogen concentration [15], also limits their application when prolonged adhesion of the clot to the tissue is required. Thus, commercial sealants based on these products vary in their proportions of thrombin and fibrinogen so as to modify product adhesion [16].…”
Section: Introductionmentioning
confidence: 99%